2006
DOI: 10.1007/s00705-006-0753-8
|View full text |Cite
|
Sign up to set email alerts
|

Analysis of VP2 gene sequences of canine parvovirus isolates in India

Abstract: The epidemiology of canine parvovirus (CPV) infections in dogs in India was examined using 27 isolates collected during a two-year period. The VP2 genes of 22 isolates were sequenced, and the deduced amino acid sequences were compared. The results indicated that the isolates belonged to CPV type 2a except four, which belonged to CPV type 2b. Comparison of the VP2 gene sequences revealed that the Indian isolates formed separate lineages distinct from the South East Asian isolates. The canine parvovirus isolates… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

11
52
5

Year Published

2008
2008
2024
2024

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 81 publications
(68 citation statements)
references
References 11 publications
11
52
5
Order By: Relevance
“…In accordance with Pinto et al (2012), the amino acid substitution Thr440Ala was not observed in any CPV-2c sequences, as previously described in CPV-2a and CPV-2b strains from Italy (Battilani et al 2002), India (Chinchkar et al 2006), Korea (Kang et al 2008), and in CPV-2c strains from Argentina (Calderón et al 2011) and Italy (Decaro et al 2009). The 440 position is located at an important VP2 domain, undergoing positive selection and envolved independently in different populations ).…”
Section: Discussionsupporting
confidence: 86%
“…In accordance with Pinto et al (2012), the amino acid substitution Thr440Ala was not observed in any CPV-2c sequences, as previously described in CPV-2a and CPV-2b strains from Italy (Battilani et al 2002), India (Chinchkar et al 2006), Korea (Kang et al 2008), and in CPV-2c strains from Argentina (Calderón et al 2011) and Italy (Decaro et al 2009). The 440 position is located at an important VP2 domain, undergoing positive selection and envolved independently in different populations ).…”
Section: Discussionsupporting
confidence: 86%
“…It was also found that CPV-2b variants are more common in Northern India especially in Bareilly region compared to CPV-2a [57,60,64]. However, these observations were in contrast with the findings of a researcher [14] who reported that CPV-2a is the major antigenic variant prevalent in Southern and Central India, based on VP2 gene sequences. Further, based on VP2 gene sequences, it was revealed that the Indian isolates formed a separate lineage distinct from the South East Asian isolates and the canine parvovirus isolates in India appear to have evolved independently without any distinct geographical patterns of evolution [14].…”
Section: Incidencementioning
confidence: 98%
“…In the 1980s, two antigenic variants of CPV-2, distinguishable using monoclonal antibodies (MoAbs), emerged almost simultaneously and were termed CPV-2a and CPV-2b [10,19]. Currently, CPV-2a is major field strain in India, Italy and Germany, while CPV-2b is common in USA, Taiwan, and Japan [2,5,7,9,15,25].…”
mentioning
confidence: 99%